Understanding individuals' incentives for climate change adaptation in Nicaragua's coffee sector. (20th April 2020) - Bro, Aniseh S.; Ortega, David L.; Clay, Daniel C.; Richardson, Robert B.
ABSTRACT: Coffee farmers who wish to become more resilient to the impacts of climate change must adopt environmentally sustainable practices that help in their adaptation to a changing environment. Among these practices is the incorporation of shade crops into coffee farms and the diversification of coffee varieties. These practices provide important services, both economic and environmental, that can contribute towards improved livelihoods. Using data from discreet choice experiments from Nicaragua, we assess farmers' willingness to change their management practices to improved practices that can help them in their adaptation to climate change. Our results show that coffee producers have heterogeneous preferences and are willing to introduce an additional shade crop and coffee varieties in their farms.